The Systems Approach as Theory for Multinational Industrial Relations in Developing Countries - Fajana, Sola (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1989)
This paper raises issues which show that the impact of the multinational companies in the industrial relations Systems of developing countries are much too profound that the Systems approach may not be suitable for explaining, predicting, and formulating policies in industrial relations in these countries in particular and beyond the level of nation states in general.